2007
DOI: 10.1007/s00420-007-0169-0
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and effort–reward-imbalance in a sample of 949 German teachers

Abstract: At present, the working situation of teachers appears to be characterized by a perceived imbalance of effort and reward and is associated with a high risk of developing burnout symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
111
3
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(142 citation statements)
references
References 20 publications
9
111
3
14
Order By: Relevance
“…Other authors also report that employees characterized by high overcommitment have a multiple elevated risk of suffering from various (psycho)somatic symptoms than their less overcommitted colleagues (Head, Kivimäki, Siegrist, Ferrie, Vahtera, Shipley and Marmot 2007;Joksimovic, Starke, von dem Knesebeck and Siegrist 2002;Kuper et al 2002;Larisch et al 2003;Li et al 2006). Highly stressed and/or overcommitted residents are more likely to experience vital exhaustion and dissatisfaction which might lead to difficulties in pursuing their chosen professional career (Preckel et al 2005;Unterbrink et al 2007). Overcommitted and stressed residents might have more difficulties establishing a good doctor-patient relationship, a factor which again contributes to feeling stressed (Jungbauer et al 2003;Jungbauer et al 2004;Langewitz, Conen, Nübling and Weber 2002).…”
Section: Work Stress and Self-reported Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors also report that employees characterized by high overcommitment have a multiple elevated risk of suffering from various (psycho)somatic symptoms than their less overcommitted colleagues (Head, Kivimäki, Siegrist, Ferrie, Vahtera, Shipley and Marmot 2007;Joksimovic, Starke, von dem Knesebeck and Siegrist 2002;Kuper et al 2002;Larisch et al 2003;Li et al 2006). Highly stressed and/or overcommitted residents are more likely to experience vital exhaustion and dissatisfaction which might lead to difficulties in pursuing their chosen professional career (Preckel et al 2005;Unterbrink et al 2007). Overcommitted and stressed residents might have more difficulties establishing a good doctor-patient relationship, a factor which again contributes to feeling stressed (Jungbauer et al 2003;Jungbauer et al 2004;Langewitz, Conen, Nübling and Weber 2002).…”
Section: Work Stress and Self-reported Healthmentioning
confidence: 99%
“…Most studies investigate the relationship between work stress and cardiovascular disease van Vegchel, de Jonge, Bosma and Schaufeli 2005), some between ERI and burnout (Unterbrink et al 2007); only a few report data on anxiety and depression (Godin and Kittel 2004;Godin et al 2005;Larisch et al 2003;Pikhart et al 2004). As far as we know, only two cross-sectional studies report the perceived effort-reward imbalance in physicians and their self-reported health (Li, Yang and Cho 2006;Rockenbauch et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Demographic characteristics such as age, sex, marital status and education have been proved to correlate with burnout to some degree 4) . Most importantly, studies have suggested that occupational stress is strongly associated with burnout in specific professional areas, such as nurses 5) and teachers 6) . Physicians, as one of the most competitive professions in the world, have also been reported to experience high levels of stress and burnout 7) .…”
mentioning
confidence: 99%
“…[13] Several researches have been conducted to assess stress levels among teachers in different countries. [14][15][16][17] In this sense, a research performed with 949 German teachers attending in primary and secondary schools found that 22% of them evaluated their occupation as extremely stressful. [14] Other investigation involving English teachers reported high occupational stress in 41.5% of the teachers' sample when compared to 32% of nurses, 28% of managers, and 27% of administrators.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] In this sense, a research performed with 949 German teachers attending in primary and secondary schools found that 22% of them evaluated their occupation as extremely stressful. [14] Other investigation involving English teachers reported high occupational stress in 41.5% of the teachers' sample when compared to 32% of nurses, 28% of managers, and 27% of administrators. [15] In Italy, researchers found that almost 25% of full-time teachers [16] and 70% of temporary teachers [17] presented high perceived stress.…”
Section: Introductionmentioning
confidence: 99%